Herbicide resistance in grain sorghum - Kershner, Kellan Scott (Kansas State University, 2011)
Sorghum acreage is declining throughout the United States because management options and yield have not maintained pace with maize improvements. The most extreme difference has been the absence of herbicide technology development for sorghum over the past twenty years. The objectives of this study were to evaluate the level of resistance, type of inheritance, and causal mutation of wild sorghums that are resistant to either acetyl-coenzyme A carboxylase (ACCase)-inhibiting herbicides or acetohydroxyacid synthase (AHAS)-inhibiting herbicides. ACCase-inhibiting herbicides used in this study were aryloxyphenoxypropionate (APP) family members fluazifop-P and quizalofop-P along with cyclohexanedione (CHD) family members clethodim and sethoxydim. The level of resistance was very high for APP herbicides but low to nonexistent to CHD herbicides. With genetic resistance to APP herbicides, the resistance factors, the ratio of resistance to susceptible, were greater than 54 to 64 for homozygous individuals and greater than 9 to 20 for heterozygous individuals. Resistance to CHD herbicides was very low with resistance factors ranging from one to about five. Genetic segregation studies indicate a single gene is the cause of resistance to APP herbicides. Sequencing identified a single mutation that results in cysteine replacing tryptophan (Trp-2027-Cys). Trp-2027-Cys has previously been reported to provide resistance to APP but not CHD herbicides. The other wild sorghum evaluated in this study was resistant to AHAS-inhibiting herbicides including imidazolinone (IM) family member, imazapyr, and sulfonylurea (SU) family member, nicosulfuron. Resistance factors in this genotype were very high, greater than 770 for the IM herbicide and greater than 500 for the SU herbicide, for both herbicide chemical families. Genetic segregation studies demonstrate that resistance was controlled by one major locus and two modifier loci. DNA sequencing of the AHAS gene identified two mutations, Val-560-Ile and Trp-574-Leu. Val-560-Ile is of unknown importance, but valine and isoleucine are similar and residue 560 is not conserved. Trp-574 is a conserved residue and Leu-574 is a known mutation that provides strong cross resistance to IM and SU herbicides. The results of these studies suggest that these sources of APP, SU, and IM resistance may provide useful herbicide resistance traits for use in sorghum.
Keywords: Target site resistance of genetic herbicide resistance; Acelolactate synthase (ALS); Herbicide resistance grain sorghum dose response; Acetohydroxyacid synthase (AHAS); Herbicide resistance weeds dose response; Acetyl-coenzyme A carboxylase (ACCase); Agronomy (0285); Genetics (0369); Plant Sciences (0479)